Ultrasonographic Discrimination of Benign and Malignant Breast Lumps with Histopathological Correlation - Yasmin, Tarana; Sultana, Sohely; Amin, Mashah Binte; Arephen, Syed Shamsul; Rafat, Sania; Farzana, Tayseer (Journal of Enam Medical College, 2015)
Background: A lump in the breast is a cause of great concern. High frequency high resolution ultrasonogram helps in its evaluation. With major advances in ultrasonographic technology during the past 20 years, ultrasonogram can now distinguish benign and malignant solid breast lumps. Knowledge of the specific benign and malignant ultrasonographic characteristics of breast lumps is imperative for accurate diagnosis and optimal patient management. Objective: To determine the validity of ultrasound in the assessment of palpable breast lump by detecting the sensitivity, specificity, accuracy, positive predictive value and negative predictive value of ultrasonogram in distinguishing benign and malignant breast lumps. Materials and Methods: This cross sectional study was done in the department of Radiology and Imaging of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in collaboration with the department of Pathology of BSMMU for histopathological correlation during July 2008 to June 2009. A total of 100 patients who were clinically suspected of having breast lump were included in this study. Data on clinical presentation, ultrasonographic findings including histopathological reports were collected and documented in structured forms. Analysis was done using SPSS 13.0 version. Results: The study was done in 100 women of 1870 years of age with mean age 41.46 ± 11.62 years. Breast lumps were found with associated clinical presentation of pain in 26 (26%) cases, discharge in 12 (12%) cases, skin changes in 28 (28%) cases, nipple retraction in 10 (10%) cases, and palpable lymph nodes in 10 (10%) cases. On ultrasonogram, lesions were diagnosed as benign in 62% cases and malignant in 38% cases. Out of sonographically diagnosed 62 benign lesions 58 (93.5%) were also proved benign histopathologically and 4 (6.5%) as malignant. Out of 38 sonographically malignant lesions, 34 (89.5%) were also proved as malignant histopathologically and 4 (10.5%) as benign. Conclusion: Ultrasonographic findings of benign and malignant breast lumps correlated well in most of the cases with the histopathological results. Therefore, it can be concluded that ultrasonogram is a useful imaging tool to discriminate benign and malignant breast lumps and thus we can reduce unnecessary breast biopsies, patient discomfort and anxiety in addition to increase in cost of the patient. J Enam Med Col 2015; 5(3): 151-156